1988
DOI: 10.1111/j.1939-1676.1988.tb02811.x
|View full text |Cite
|
Sign up to set email alerts
|

Recording of Visual‐Evoked Potentials in Dogs With Scalp Electrodes

Abstract: Following unsuccessful attempts to record visual-evoked potentials (VEPs) in dogs with scalp electrodes, adoption of a new stimulation technique seems to be beneficial. Previously, flashes of white light administered after dark adaptation induced relatively high amplitude electroretinograms (ERGs) covering any VEP activity over the surface of the skull. ERG amplitude, however, can be significantly reduced using flashes of red light after light adaptation (mostly cone stimulation). Simultaneous ERG and VEP reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
5

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
2
14
0
5
Order By: Relevance
“…Our current data confirm that, via extensive behavioral training with positive reinforcement, it is possible to conduct non-invasive EEG measurement and group-level studies with fully conscious, non-medicated and unrestrained domestic dogs—an endeavor that has been deemed unsuccessful in the past [14], [34]. In our study, the training and the EEG recordings were optimized for the relatively short attention span, as well as vibrant habitude of dogs, compared with the standard measurements in human subjects.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our current data confirm that, via extensive behavioral training with positive reinforcement, it is possible to conduct non-invasive EEG measurement and group-level studies with fully conscious, non-medicated and unrestrained domestic dogs—an endeavor that has been deemed unsuccessful in the past [14], [34]. In our study, the training and the EEG recordings were optimized for the relatively short attention span, as well as vibrant habitude of dogs, compared with the standard measurements in human subjects.…”
Section: Discussionsupporting
confidence: 71%
“…Brain function of dogs has been studied in the past mainly by recording activity with electroencephalography (EEG) directly from the brain, by sedating the animals and restraining their movements, and by putting them down after the experiment. Most of the functional brain research of dogs has explored epilepsy [e.g., [11], although some studies have described features of the nervous system functionality, such as oscillatory EEG activity during sleep [12] or awake state [13], or visual evoked potentials to flashes of light [14][16]. However the intracranial measurements, with the need to restrain and medicate the animals, do not readily allow the study of the nervous system function during cognitive events.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study described VEP recorded from anesthetized dogs in response to flashes of red light. 26 The authors reported an inability to record reliable responses in conscious or sedated dogs, and described three negative peaks in the VEP that were inconsistently present in all dogs. They proposed that their stimulation protocol would reduce masking of early VEP components by farfield ERG signals, as reported in their earlier s t~d y .~ Because both studies used general anesthesia (halothane or chloralose), which, as the authors reported, may affect VEP recordings, it is difficult to draw conclusions from their results.…”
Section: Discussionmentioning
confidence: 99%
“…The flash VEP stimulated by the flashlight has also been recorded in dogs [1,5,6,[9][10][11], however the generators of potentials in amplitude and/or latency of the waves, are not well known. Recently, topographic analysis of evoked potentials have been applied in human using multiple electrodes on the scalp for elucidating generators of the waves in the flash VEP [3,7,8,12].…”
mentioning
confidence: 99%